The Influence of Parental Assistance on Interest in Learning to Read and Write the Qur'an for MI/SD Level Students - Hardiansyah; Sriyanti (Journal of Contemporary Islamic Primary Education, 2022)
The role of parents is the role of the main educator who will be responsible for their children. Parents are responsible for their children to guide especially in children's learning. This study used quantitative research with a population of all students at MIS Az-Zuhri, Medan Sinembah Village, totaling 163 students and taking a sample of 27 students with a random sampling technique. Data collected using a questionnaire instrument and documentation. The role of parents of students is good with an average value of 68.74 while students' interest in learning is also good with an average value of 66. The results of the study found that the influence of parental assistance on the interest in learning to read and write the Qur'an for Madrasah Ibtidaiyah Az students -Zuhri. Medan Sinembah village is influential. positive and significant with the value of the correlation coefficient. r equal to 0.507 and value. significant at .0.007 or' <0.05.